Psychiatric health care center and nursing home - differences and similarities - Siejko, Krzysztof; Drop, Bartłomiej; Dubas-Ślemp, Halina; Książek, Piotr; Kos, Marek; Tylec, Aneta (Polish Journal of Public Health, 2017)
The authors will try to introduce the subject and provide arguments that will show the differences and similarities between psychiatric health care center and nursing home, as Polish society often wrongly use those two different types of institutional support interchangeably.Both, health care center and nursing home offer round-the-clock services, but they differ in scope of activity. The knowledge of the profile of institutional units should be an essential argument when choosing the type of institution. The basic criterion for admission to the health care center (psychiatric or somatic) are medical condition, the presence of the disease and the need for continued treatment. While the cause of referring to the nursing home is, or in many cases should be, the life incapability, the lack of support of the home environment or homelessness.Awareness to the highest quality of care and support should be an overarching value of all institutions, both health care and social welfare and the standards of care and support should contribute to changing society’s attitude to this type of institutions.